2015
DOI: 10.1080/01694243.2015.1071023
|View full text |Cite
|
Sign up to set email alerts
|

A holistic mathematical modelling and simulation for cathodic delamination mechanism – a novel and an efficient approach

Abstract: This paper addresses a holistic mathematical design using a novel approach for understanding the mechanism of cathodic delamination. The approach employed a set of interdependent parallel processes with each process representing: cation formation, oxygen reduction and cation transport mechanism, respectively. Novel mathematical equations have been developed for each of the processes based on the observations recorded from experimentation. These equations are then solved using efficient time-iterated algorithms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Khan-Nazir [17], recently developed an efficient time iterative model and showed that the concentration of cations (e.g. Na + in NaCl solution) and their transport significantly affect the debonding of film-substrate system thus deciding delamination rate.…”
Section: Cathodic Delaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Khan-Nazir [17], recently developed an efficient time iterative model and showed that the concentration of cations (e.g. Na + in NaCl solution) and their transport significantly affect the debonding of film-substrate system thus deciding delamination rate.…”
Section: Cathodic Delaminationmentioning
confidence: 99%
“…In the case of cathodic delamination, separation of the film is linked to the cathodic reaction in a localized corrosion cell. As such, cathodic delamination [17,129,130] is closely related to the phenomena of cathodic blistering [16,18,21]. Tribocorrosion degradation is linked to the mechanical wear and the electrochemical corrosive degradation of films.…”
Section: Future Scientific Challenges In Degradation Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pervious research has analysed [36][37][38][39][40][41][42][43][44][45] coating substrate system without the inclusion of micro-cracks. However, this research aims to analyse the coupling effects of residual and diffusion induced stresses on blister growth in the presence of coating micro-cracks.…”
Section: Introductionmentioning
confidence: 99%
“…blistering, delamination, micro-cracks and corrosion damage measurement in real time has been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently a simplistic model of variation in environmental parameters to understand the effects of changing relative humidity and temperatures in terms of corrosion initiation and propagation on bare steel samples has been published [8].…”
Section: Introductionmentioning
confidence: 99%